2020
DOI: 10.1155/2020/3071658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Exercise Loads on Testicular Oxidative Stress and Reproductive Function in Obese Male Mice

Abstract: This study is aimed at investigating the effect of different exercise loads on the reproductive function of obese male mice and the underlying mechanisms. Male mice with high-fat diet-induced obesity were divided into obesity control (OC), obesity moderate-load exercise (OME), and obesity high-load exercise (OHE) groups. The OME and OHE groups were subjected to swimming exercise 5 days per week over a duration of 8 weeks, with the exercise load progressively increased to 2 h per day in the OME group and 2 h tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 53 publications
4
28
2
1
Order By: Relevance
“…The short and long-term high-fat diet increased Leydig cell pathological damage, apoptosis rate in addition to oxidative stress in testis tissue and high leptin level may provide some evidence to clarify the mechanisms of male secondary hypogonadism in obesity ( Pinto-Fochi et al., 2016 ). Moreover, Yi et al. (2020) recorded that animals fed high fat diet or high cholesterol diet recorded lower testosterone level and attributed this effect to the oxidative effect of these diets.…”
Section: Discussionmentioning
confidence: 99%
“…The short and long-term high-fat diet increased Leydig cell pathological damage, apoptosis rate in addition to oxidative stress in testis tissue and high leptin level may provide some evidence to clarify the mechanisms of male secondary hypogonadism in obesity ( Pinto-Fochi et al., 2016 ). Moreover, Yi et al. (2020) recorded that animals fed high fat diet or high cholesterol diet recorded lower testosterone level and attributed this effect to the oxidative effect of these diets.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification was performed on the ABI 7500 thermocycler (Applied Biosystems) with the following procedure: pretreatment at 50°C for 2 min, pre‐denaturation at 95°C for 10 min, denaturation at 95°C for 15 s and annealing at 60°C for 60 s, with 40 cycles in total. At the end of the programme, the CT value of the target gene and the internal reference (GAPDH) were standardised to calculate the relative expression of the target gene (Yi et al., 2020). Primers for StAR, P450scc, 3β‐HSD, StARD7 and GAPDH were designed and synthesised by Shanghai Bioengineering.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study showed that moderate- and heavy-load exercise increased energy consumption and reduced body fat in obese mice. However, only moderate-load exercise significantly improved gonadal hypofunction in obese male mice, while high-load exercise showed no significant effect [ 9 ]. The mechanism underlying this phenomenon was not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, tumor necrosis factor-alpha (TNF-α) and interleukin-1 (IL-1) decreased GnRH secretion by downregulating kisspeptin signaling in the hypothalamus [ 19 , 20 ]. Moreover, a long-term positive energy balance can lead to the development of leptin resistance and chronic inflammatory response, both of which are closely related to exercise [ 9 , 21 ]. However, whether the two can work together to regulate the energy balance of the hypothalamic kiss neurons and regulate male reproductive function is unknown.…”
Section: Introductionmentioning
confidence: 99%